2010
DOI: 10.1016/j.febslet.2010.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial potassium channels and reactive oxygen species

Abstract: a b s t r a c tPretreatment of tissues with potassium channel openers (KCO's) has been observed to be cytoprotective in a broad variety of insults. This phenomenon has been proposed to be intimately linked to activation of mitochondrial potassium channels which apparently modulate the mitochondrial production of reactive oxygen species (ROS). This critical review summarizes literature findings about the mitochondrial production of ROS, the action of KCO's on mitochondrial ROS production and the putative link t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(54 citation statements)
references
References 55 publications
1
47
0
2
Order By: Relevance
“…In particular, mito K ATP , mito BK Ca , and mito Kv1.3 channels have been proposed as potential targets of neuroprotective approaches (14,15). Under pathological conditions, enhanced cytosolic Ca 2ϩ concentrations result in loss of mitochondrial membrane potential (⌬⌿ m ), decreased ATP levels, formation of reactive oxygen species (ROS), and failure of the mitochondrial Ca 2ϩ retention capacity.…”
mentioning
confidence: 99%
“…In particular, mito K ATP , mito BK Ca , and mito Kv1.3 channels have been proposed as potential targets of neuroprotective approaches (14,15). Under pathological conditions, enhanced cytosolic Ca 2ϩ concentrations result in loss of mitochondrial membrane potential (⌬⌿ m ), decreased ATP levels, formation of reactive oxygen species (ROS), and failure of the mitochondrial Ca 2ϩ retention capacity.…”
mentioning
confidence: 99%
“…It has been reported that a collapse of ΔΨm, resulting from mitoK ATP channel opening, leads to mitochondrial respiratory chain disorders associated with an increase in complex III-dependent ROS and a decrease in complex I-dependent ROS (21). Thus, complex III is considered to be a major ROS-releasing site during phases of decreased membrane potential mediated by mitoK ATP channel opening (28).…”
Section: Discussionmentioning
confidence: 99%
“…ROS has been implicated as a trigger that causes aberrant proliferation or apoptotic resistance in hPASMCs under hypoxic conditions (28). It has been reported that a collapse of ΔΨm, resulting from mitoK ATP channel opening, leads to mitochondrial respiratory chain disorders associated with an increase in complex III-dependent ROS and a decrease in complex I-dependent ROS (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kv 1.3 ve benzeri büyük potasyum kanalları, direkt hedefleri olan ve mitokondride bulunan pro-apoptotik özellikteki Bax ve Bad proteinleriyle beraber hücre ölümünde rol oynayabilmektedir [24]. Mitokondrial iç zarda bulunan Kv 1.3 potasyum kanalının inhibisyonu sonucunda da ROS miktarlarının arttığı çeşitli çalışmalarla desteklenmiştir [25][26][27][28]. Kv 1.3 potasyum kanalı kadar periferal kan lenfositlerinde, makrofajlarda, kanser olmayan ve kanser hücre hatlarının mitokondrisinde bulunan Kv 1.3 kanalının eksprese olduğu bildirilmiştir [29].…”
Section: Introductionunclassified